2024
DOI: 10.32479/ijeep.15049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Renewable and Non-Renewable Energy Resources on CO2 Emission: Empirical Evidence from SAARC

Ahsan Akbar,
Azeem Gul,
Mariam Sohail
et al.

Abstract: When assessing sustainability performance, researchers often ignore the implications of combining energy, economic, and environmental factors. To address this void, we assess the consequence of energy dis-aggregation proceeding carbon emissions in SAARC nations. The majority of energy resources are renewable and non-renewable, which contributes to a rise in carbon dioxide emissions. This study aims to provide a thorough understanding of the energy utilization dioxide emissions nexus. The panel data sets coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Many studies have concluded that economic growth and non-renewable energy consumption increase carbon emissions. Some of these studies have been conducted on a countryby-country basis (Ali et al, 2016;Amirnia, 2023;Mushtaq & Ahmed, 2021;Omri & Saadaoui, 2023;Shahbaz et al, 2013;Shahzad et al, 2017;Wen et al, 2021) and some on a country group basis (Akbar et al, 2024;Alola et al, 2019;Amin & Song, 2023;Godil et al, 2021). Studies on the impact of renewable energy consumption on carbon emissions and these variables have started to be widely included in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have concluded that economic growth and non-renewable energy consumption increase carbon emissions. Some of these studies have been conducted on a countryby-country basis (Ali et al, 2016;Amirnia, 2023;Mushtaq & Ahmed, 2021;Omri & Saadaoui, 2023;Shahbaz et al, 2013;Shahzad et al, 2017;Wen et al, 2021) and some on a country group basis (Akbar et al, 2024;Alola et al, 2019;Amin & Song, 2023;Godil et al, 2021). Studies on the impact of renewable energy consumption on carbon emissions and these variables have started to be widely included in the literature.…”
Section: Introductionmentioning
confidence: 99%